2019
DOI: 10.1371/journal.pone.0209905
|View full text |Cite
|
Sign up to set email alerts
|

Viable Neisseria meningitidis is commonly present in saliva in healthy young adults: Non-invasive sampling and enhanced sensitivity of detection in a follow-up carriage study in Portuguese students

Abstract: Introduction and aimsImproved sensitivity and efficiency of detection and quantification of carriage of Neisseria meningitidis (Nm) in young people is important for evaluation of the impact of vaccines upon transmission and associated population-wide effects. Saliva collection is quick, non-invasive and facilitates frequent sampling, but has been reported to yield low sensitivity by culture. We re-evaluated this approach in a follow-up cross sectional study using direct and culture-amplified PCR.Material/Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…Although numerous studies have implicated oral fluids in meningococcal transmission [8][9][10][11][12][13][14][15][16], very few actually tested saliva as specimen for assessing meningococcal carriage [18,19]. In this context, our findings are in line with a meningococcal carriage study conducted recently by Rodrigues et al [20]. Among 299 students, we observed an overall meningococcal carriage rate of 24.7%, a prevalence that is in line to what has been reported previously with pharyngeal swabs for this age group [2,15].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Although numerous studies have implicated oral fluids in meningococcal transmission [8][9][10][11][12][13][14][15][16], very few actually tested saliva as specimen for assessing meningococcal carriage [18,19]. In this context, our findings are in line with a meningococcal carriage study conducted recently by Rodrigues et al [20]. Among 299 students, we observed an overall meningococcal carriage rate of 24.7%, a prevalence that is in line to what has been reported previously with pharyngeal swabs for this age group [2,15].…”
Section: Discussionsupporting
confidence: 91%
“…In this context, our findings are in line with a meningococcal carriage study conducted recently by Rodrigues et al . [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparison of swabbing sites between the posterior pharynx behind the uvula and the posterior pharynx behind the uvula and one tonsil, in a direct comparison in Mali, identified that carriage where only one site is swabbed may underestimate carriage rates 41 . Alternative samples, such as saliva, are rapid, inexpensive, and non-invasive but there are conflicting reports on their effectiveness for detecting carriage of Neisseria 4244 . The UKMenCar surveys sought to optimize the site of swabbing by taking a sweep of the posterior pharynx from one tonsil to the other.…”
Section: Discussionmentioning
confidence: 99%
“…Density of N. meningitidis pharyngeal carriage varies, with the majority of those colonised having relatively small amounts of bacteria present. [20,21] Pneumococcal conjugate vaccines have demonstrated a reduction in carriage density of vaccine-type strains of pneumococci in a small number of studies, [22][23][24] but not all. [25,26] Mucosal immune responses to recombinant vaccines may be different to that of conjugate vaccines.…”
Section: Introductionmentioning
confidence: 99%